Rare earth magnet
By aligning the easy magnetization shaft of R-Fe-B alloy by thermoplastic processing, the problem of degradation of magnetic characteristics after grinding of Nd-Fe-B system sintered magnets is solved, and the manufacturing of high-performance rare earth magnets is realized, which simplifies the process flow and Reduces magnetic properties loss.
Patent Information
- Application Number
- CN202380044600.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-14
AI Technical Summary
The magnetic properties of the existing Nd-Fe-B-type sintered magnets decrease after grinding, and additional heat treatment and film layer coverage are required to increase operational complexity.
Through thermoplastic processing, the easy magnetization axis of R-Fe-B alloy is aligned toward the short axis of the grain, reducing the impact of grinding processing on magnetic characteristics, and avoiding additional heat treatment and film layer coverage, directly realizing high-performance rare earths. magnet.
It realizes high performance and excellent workingability of rare earth magnets, reduces magnetic properties loss, and is suitable for ultra-small/thin motors and magnetic actuators.
Smart Images

Figure CN119317980A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to rare earth magnets. Background Art
[0002] Nd-Fe-B permanent magnets have excellent magnetic properties and are therefore used in computer-related equipment, various electronic devices, home appliances, and various actuators. In recent years, there has been a desire and demand for miniaturization and thinning of these electronic devices, home appliances, and various actuators, and there is a particular demand for miniaturization and thinning of sintered magnets with excellent magnetic properties among Nd-Fe-B permanent magnets.
[0003] In the past, when miniaturizing and thinning Nd-Fe-B system sintered magnets, it was generally necessary to cut the sintered block magnet into a specified shape and then grind the surface to form a desired thickness. However, it is known that the more the Nd-Fe-B system sintered magnet is ground to make it thinner, the lower the magnetic properties of the sintered magnet (for example, refer to Patent Document 1).
[0004] Patent document 1 discloses the following: In order to prevent the deterioration of magnetic properties caused by grinding, an alloy thin film layer containing 1.0 atomic % to 50.0 atomic % of at least one of Ti, W, Pt, Au, Cr, Ni, Cu, Co, Al, Ta and Ag and the remainder consisting of R' (R' is at least one of Ce, La, Nd, Pr, Dy, Ho and Tb) is formed on the ground surface of the sintered magnet body.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 62-192566 Summary of the invention
[0008] Problems to be solved by the invention
[0009] However, Patent Document 1 lists as a solution for coating the ground surface of a sintered magnet body with an alloy thin film layer, a thin film forming method such as vacuum evaporation, ion sputtering, ion plating, ion evaporation thin film forming method, plasma evaporation thin film forming method, etc., which can be appropriately selected. After the alloy thin film layer is formed, it is necessary to perform a heat treatment at least once at 400°C to 900°C for 1 minute to 3 hours in a vacuum or inert environment.
[0010] As described above, an additional operation step is required after grinding the surface of the sintered magnet to a desired thickness, which deteriorates the workability.
[0011] Therefore, an object of the present invention is to provide a high-performance rare earth magnet that is excellent in workability during production.
[0012] Solutions for solving problems
[0013] In order to solve the above problems and achieve the purpose, a rare earth magnet according to one embodiment of the present invention is a rare earth magnet obtained by hot plastic processing of an R-Fe-B alloy containing R (R represents a rare earth element including Nd), Fe and B, wherein the rare earth magnet has a 14 The structure of the main phase of the B compound is such that the easy magnetization axis is oriented toward the short axis direction of the grains of the above main phase, the thickness dimension in the direction of the easy magnetization axis is greater than 0.07 mm and less than 0.2 mm, and the reduction rate of residual magnetization is less than 5% (wherein the reduction rate of residual magnetization (%) is the ratio of the reduction relative to the residual magnetization when the above thickness dimension of the above rare earth magnet is 0.5 mm being set to 100%).
[0014] Effects of the Invention
[0015] According to one aspect of the present invention, a high-performance rare earth magnet having excellent workability during production can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a diagram schematically showing a cross-sectional view in the thickness direction of a rare earth magnet according to an embodiment.
[0017] Figure 2 This is a diagram schematically showing a cross-sectional view in the thickness direction of a rare earth magnet obtained when a surface parallel to the thickness direction of a flat plate is processed in a grinding process.
[0018] Figure 3 This is a diagram schematically showing a cross-sectional view in the thickness direction of a Nd sintered magnet subjected to a grinding process.
[0019] Figure 4 It is a graph showing the demagnetization curve of the test piece of the example.
[0020] Figure 5 This is a diagram showing a demagnetization curve of a test piece of a comparative example (a test piece produced using sample A).
[0021] Figure 6 This is a diagram showing a demagnetization curve of a test piece of a comparative example (a test piece produced using sample B). DETAILED DESCRIPTION
[0022] Hereinafter, the embodiments of the present invention will be described in detail based on the accompanying drawings. It should be noted that the present invention is not limited to the embodiments. In addition, the constituent elements of the following embodiments include elements that can be replaced and easily replaced by those skilled in the art or substantially the same elements.
[0023] The rare earth magnet (also referred to as rare earth permanent magnet) of the embodiment is a rare earth magnet obtained by hot plastic working an R-Fe-B alloy containing R (R represents a rare earth element including Nd), Fe, and B. Specifically, it can be produced by the following method.
[0024] <Production of rare earth magnet powder>
[0025] First, R-Fe-B magnet powder is prepared as rare earth magnet powder. The R-Fe-B (boron) magnet constituting the R-Fe-B magnet powder contains R2Fe 14 B phase (such as R2Fe 14 B-type compound phase) as the main phase. In addition, R-Fe-B system magnets usually also contain R-rich phases, etc. R represents a rare earth element containing Nd. That is, R contains Nd as an essential component. As rare earth elements, in addition to neodymium (Nd) and praseodymium (Pr), scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu) can be listed. One other rare earth element can be used together with Nd, or two or more can be used in combination. As R, at least Nd can be used. A portion of Fe can be replaced by Co. When a portion of Fe is replaced by Co, when the total amount of Fe and Co is set to 100 atomic %, it is preferred to contain Fe in an amount of 50 atomic % or more.
[0026] R-Fe-B magnets may also contain other elements. Examples of other elements include titanium (Ti), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf), tantalum (Ta), and tungsten (W). Other elements may be used alone or in combination of two or more. In R-Fe-B magnets, it is preferred that R be contained in an amount of 12 atomic % or more and 16 atomic % or less. It is preferred that B be contained in an amount of 6 atomic % or more and 8 atomic % or less. In addition, when the above-mentioned other elements are contained, it is preferred that the other elements be contained in an amount of more than 0 atomic % and less than 3 atomic %. It should be noted that, here, the remainder is the total amount of Fe and the elements inevitably contained.
[0027] Here, as an R-Fe-B system magnet, for example, an Nd-Fe-B system magnet using an Nd-Fe-B system alloy having Nd2Fe14B as a main phase will be described as an example.
[0028] Nd-Fe-B magnet powder is manufactured, for example, by ultra-quenching method (melt spinning method). Specifically, the Nd-Fe-B alloy is melted by high-frequency induction heating under negative pressure or in an argon environment. Then, the melted alloy is sprayed onto a copper rotating roller for ultra-quenching (high-speed cooling) to produce a ribbon-shaped thin strip. Then, the thin strip is crushed. For example, it is preferred to break the thin strip into pieces of about several mm to tens of mm and then crush them with a crusher. The thin strip is crushed to obtain a crushed powder.
[0029] After the ribbon-shaped thin ribbon pieces are crushed to obtain crushed powder, they are heat-treated to obtain magnetic powder. At this stage, the directions of the easy magnetization axes of each grain of the magnetic powder have not yet been aligned in one direction, so they are magnetically isotropic. It should be noted that the actual production of magnetic powder can be replaced by pre-made magnetic powder. For example, Magnequench provides magnetic powder that is magnetically isotropic by crushing a thin ribbon of Nd-Fe-B produced by ultra-quenching in the form of magnetic powder with increased density through hot pressing.
[0030] <Hot Pressing Process: Production of Sintered Magnets>
[0031] Next, prepare the first mold. The first mold is composed of a hollow cylindrical die, a hollow cylindrical upper punch and a lower punch inserted into the inner side of the die, and a cylindrical core arranged inside the upper punch and the lower punch. The die, the upper punch, the lower punch and the core are formed of a conductive material (such as graphite, superhard alloy, etc.).
[0032] Next, rare earth magnet powder (Nd—Fe—B magnet powder) is filled into a first mold and placed in a sintering device (SPS device: spark plasma sintering device) for sintering, and a sintered magnet (hot pressed magnet) is taken out from the first mold.
[0033] The magnetic powder filled in the cavity of the first mold is pressurized by the upper punch and the lower punch by the pressure applied between the upper electrode and the lower electrode. In addition, the current flows from the upper electrode to the upper punch, and the current flows to the die, the iron core and the magnetic powder, and flows to the lower electrode via the lower punch, thereby generating Joule heat, and generating discharge plasma in the magnetic powder, thereby heating the magnetic powder. For example, while applying pressure at 30 to 50 MPa, it is heated to 600 to 700°C (hot pressing). In addition, it is preferred to sinter under negative pressure and in an inert environment, and specifically, it is preferred to sinter in an argon or nitrogen environment.
[0034] After heating, the current is cut off and the magnet is cooled. After cooling to a predetermined temperature, the first mold is taken out from the sintering device. Specifically, the annular sintered magnet body formed by sintering the magnet powder is taken out from the first mold. The annular sintered magnet body in this state is, for example, an outer diameter of Φ30 mm×an inner diameter of Φ15 mm×a thickness of 10 mm, and its relative density is about 90%. The orientation of the easy magnetization axis of its grains is random and the magnetism is isotropic.
[0035] <Thermoplastic processing process: Production of hot-processed magnets>
[0036] Next, the second mold is prepared. It should be noted that the preparation of the second mold may be performed in parallel with the preparation of the first mold, or may be performed before the preparation of the first mold.
[0037] The sintered magnet body produced by the hot pressing step is placed in a second mold, and the second mold is placed in a sintering device to perform hot plastic processing.
[0038] In the sintering device, an upper electrode is arranged at the upper end of the punch, and a lower electrode is arranged at the lower end of the die. The upper electrode and the lower electrode are formed of a conductive material (such as graphite, superhard alloy, etc.). The sintering device includes: a power supply device that applies a predetermined voltage between the upper electrode and the lower electrode to supply a predetermined current; and a control device. The sintering device can be used as the sintering device in the above-mentioned hot pressing process, or it can be another device.
[0039] The sintered magnet body disposed between the die and the punch of the second die is pressurized by the die and the punch. In addition, heating is performed by discharge plasma and Joule heat generated by the flow of current in the path of the upper electrode → punch → sintered magnet body → die → lower electrode. Thermoplastic processing starts heating after applying a pressure of 30MPa to 100MPa, for example, while heating to above 600°C and below 700°C, pressurization is performed. During heating, the sintered magnet body is energized with on-off (ON-OFF) DC pulses. In thermoplastic processing, it is ideal to adjust the pressure in a manner that does not increase the processing speed, preferably in a manner that keeps the processing speed constant. Preferably, the thermoplastic processing is performed under negative pressure or in an inert environment, specifically in an argon or nitrogen environment. Preferably, the thermoplastic processing is performed after the displacement starts until the displacement is completed while monitoring the displacement. Here, with respect to the monitoring of the displacement, the displacement of the servo motor that performs the pressure control is usually monitored.
[0040] The grains of the hot-processed magnet produced by thermoplastic processing have a flat shape, and the easy magnetization axis of the grains is oriented in a direction perpendicular to the flat surface of the grains. The grains when the thin strip is made by ultra-rapid cooling are isotropic in shape, but through thermoplastic processing, the grains grow into a flat shape, and the flat surfaces of the particles are mechanically aligned in the direction of pressure. That is, it means that the pressure direction (the short axis direction of the grains) is aligned with the easy magnetization axis. Therefore, the easy magnetization axis of the grains in the magnet is aligned with the thickness direction of the hot-processed magnet (the sintered magnet body is changed into a hot-processed magnet through thermoplastic processing). It should be noted that the hot-processed magnet is a magnet that uses the manufacturing method of making anisotropic magnets by so-called hot extrusion processing.
[0041] After heating, the sintering device is cooled by cutting off the current. After cooling to a predetermined temperature, the second mold is removed from the sintering device, and the ring-shaped hot-processed magnet obtained by hot plastic processing of the sintered magnet body is removed from the second mold.
[0042] The hot-working magnet obtained by hot plastic working has anisotropy in magnetism, and its shape is, for example, outer diameter Φ40mm×inner diameter Φ11mm×thickness 3mm, and its relative density is close to true density, and its magnetic properties are high. The average crystal grain size of the hot-working magnet produced is 0.02μm or more and 0.5μm or less, and the Curie point is 250℃ or more and 400℃ or less.
[0043] <Grinding process>
[0044] The hot-processed magnet obtained by hot plastic processing is ground into a specified shape. Specifically, the hot-processed magnet after hot processing is taken out from the device, and the hot-processed magnet is placed in a wire cutting device and cut into a specified shape. For example, it is cut into a flat plate of 2mm×2mm square to 10mm×10mm square with a thickness of more than 1mm and less than 5mm. Here, the thickness direction of the flat plate is cut in a manner consistent with the thickness direction of the hot-processed magnet (the direction of pressure applied when the hot-processed magnet is made, that is, the direction of the easy magnetization axis).
[0045] Next, the two end faces (the faces in the direction perpendicular to the thickness direction of the plate) of the cut plate are ground using a surface grinder to form a desired thickness dimension. That is, the thickness dimension after grinding is greater than 0.07 mm and less than 0.2 mm, preferably greater than 0.1 mm and less than 0.2 mm. In detail, grinding is performed only in the short axis direction of the flat grains in the hot-processed magnet. Grinding is performed, for example, using a rotating grinding wheel including a diamond grinding wheel.
[0046] The rare earth magnet of the embodiment can be obtained by the above-mentioned method, for example, and thus has a structure including R2Fe 14The structure of the main phase of the B compound. In addition, the average grain size of the main phase is preferably 0.02 μm or more and 0.5 μm or less. In addition, the easy magnetization axis of the rare earth magnet of the embodiment is oriented in the short axis direction of the grains of the main phase. Moreover, the thickness dimension in the direction of the easy magnetization axis is 0.07 mm or more and 0.2 mm or less. It should be noted that it is preferably a flat plate of 2 mm × 2 mm square to 10 mm × 10 mm square.
[0047] In addition, the reduction rate of residual magnetization of the rare earth magnet of the embodiment is 5% or less. In this way, the reduction rate of residual magnetization of the rare earth magnet of the embodiment is suppressed to be small and the performance is high. Here, the reduction rate (%) of residual magnetization is calculated as follows. First, the residual magnetization of the rare earth magnet is measured when the thickness dimension is 0.5 mm. It should be noted that the rare earth magnet with a thickness dimension of 0.5 mm can be specifically prepared as a sample whose thickness dimension is adjusted to 0.5 mm in the grinding process of the rare earth magnet of the embodiment. Next, the residual magnetization of the rare earth magnet of the embodiment is measured. Next, the residual magnetization of the rare earth magnet with a thickness dimension of 0.5 mm is set to 100%, and the ratio of the reduction of the residual magnetization of the rare earth magnet of the embodiment is calculated relative to this. For example, when the residual magnetization of the rare earth magnet with a thickness dimension of 0.5 mm is set to 100%, the residual magnetization of the rare earth magnet of the embodiment is 95%, and the reduction rate of residual magnetization is 5% (100%-95%).
[0048] The thickness of the rare earth magnet in the embodiment in the direction of the easy magnetization axis is preferably 0.1 mm to 0.2 mm, and the reduction rate of residual magnetization is 1% or less. If the thickness in the direction of the easy magnetization axis is within the above range, the reduction rate of residual magnetization can be further suppressed.
[0049] The reason why the reduction rate of residual magnetization can be suppressed even with a small thickness in the rare earth magnet of the embodiment is considered to be as follows. Figure 1 Schematically showing a cross-sectional view of a rare earth magnet according to an embodiment of the present invention in the thickness direction. In the rare earth magnet according to the embodiment of the present invention, the flat crystal grains 10 are stacked in such a manner that their minor axis direction (easy magnetization axis) is aligned with the thickness direction of the flat rare earth magnet. Figure 1 The upward arrow in the figure indicates the direction of the easy magnetization axis. In the grinding process, the surface perpendicular to the thickness direction of the plate is processed, so the grains exposed on the processed surface after processing will deteriorate. Figure 1 denoted by the crystal grains 12 degraded by grinding. It is considered that in the rare earth magnet of the embodiment, the portion occupied by the crystal grains 12 degraded by grinding is small, and therefore the reduction rate of residual magnetization can be suppressed.
[0050] on the other hand, Figure 2This is a diagram schematically showing a cross-sectional view in the thickness direction of a rare earth magnet obtained when a surface parallel to the thickness direction of a flat plate is processed in a grinding process. It should be noted that, Figure 2 The upward arrow in the figure indicates the direction of the easy magnetization axis. Considering that in this case, the portion occupied by the grains 12 deteriorated by grinding becomes larger, so it is difficult to suppress the rate of decrease of residual magnetization. Based on the above, it is considered that since the grains 10 are flat, the degradation caused by processing is also reduced when the easy magnetization axis is aligned with the processing surface like the rare earth magnet of the embodiment, and the rate of decrease of residual magnetization can be suppressed.
[0051] Furthermore, as a comparison, a case where a magnet having the same size as the rare earth magnet of the embodiment is obtained by grinding an Nd sintered magnet will be described. Figure 3 Schematically shows a cross-sectional view in the thickness direction of a Nd sintered magnet subjected to a grinding process. Figure 3 The upward arrow in the figure indicates the direction of the easy magnetization axis. The shape of the grain 20 of the Nd sintered magnet is roughly isotropic. In the grinding process, the processing is performed in the direction of the easy magnetization axis. The grains exposed on the processed surface after processing are deteriorated. Figure 3 In the figure, it is indicated that the grains 22 deteriorated by grinding are present. Considering that the portion of the grains 22 deteriorated by grinding in the Nd sintered magnet is large, the rate of decrease of residual magnetization is also large. It should be noted that the shape of the grains 20 of the Nd sintered magnet is approximately isotropic, so it is considered that the deterioration caused by grinding does not depend on the easy magnetization axis and the processed surface.
[0052] Thus, the rare earth magnet of the embodiment does not form an alloy thin film layer on the surface or perform heat treatment, and has excellent workability during manufacturing. In addition, even if the thickness dimension is small, the reduction rate of residual magnetization can be suppressed, and the performance is high. Therefore, the rare earth magnet of the embodiment is suitable as a magnet for ultra-small / thin motors, ultra-small / thin magnetic actuators, etc.
[0053] [Example]
[0054] <Preparation of test pieces in examples>
[0055] As described above, Nd-Fe-B magnet powder (having a magnet powder containing R2Fe 14B compound as the main phase) to make a sintered magnet body, and a hot-processed magnet is made by hot plastic processing. Next, the hot-processed magnet obtained by hot plastic processing is cut into a sample piece of a specified flat plate shape (3mm×3mm). Here, it is cut in a manner that the thickness direction of the flat plate is consistent with the thickness direction of the hot-processed magnet (the direction of pressure when the hot-processed magnet is made, that is, the direction of the easy magnetization axis). Next, a sample piece (3mm×3mm×thickness t) is made by grinding. Specifically, a test piece in which the thickness t of the sample piece is changed to 0.5mm, 0.2mm, 0.1mm and 0.07mm is made. It should be noted that the test piece is a material containing R2Fe 14 A rare earth magnet having a main phase structure of a B compound and an easy magnetization axis oriented in the direction of the short axis of the crystal grains of the main phase. In addition, the average crystal grain size of the main phase is 0.02 μm or more and 0.5 μm or less.
[0056] <Preparation of test pieces for comparison>
[0057] The test pieces for comparison are made using sample A and sample B. Sample A and sample B are both Nd-Fe-B sintered magnets manufactured by Shin-Etsu Chemical Co., Ltd., which are magnetically anisotropic. The model of sample A is N50, and the model of sample B is N39UH. A sample piece of a specified shape (3mm×3mm) is cut from a block having the specified shape. Here, the cutting is performed in such a way that the thickness direction of the flat plate is consistent with the direction of the easy magnetization axis. Next, a sample piece (3mm×3mm×thickness t) is made by grinding. Specifically, test pieces with thickness t changed to 0.5mm, 0.2mm, 0.1mm, and 0.07mm are made.
[0058] <Measurement of magnetic properties>
[0059] A magnetic field of 5 T was applied to each sample piece to magnetize it in the thickness direction (direction of easy magnetization axis) of the sample piece, and then the magnetic properties of the sample piece were measured using a vibrating sample magnetometer (VSM). Figures 4 to 6 Indicates the result. That is, Figure 4 The demagnetization curve of the test piece of the embodiment is shown. Figure 5 The demagnetization curve of the test piece of the comparative example (the test piece prepared using the sample A) is shown. Figure 6 The demagnetization curve of the test piece of the comparative example (the test piece produced using the sample B) is shown.
[0060] like Figures 4 to 6As shown in the figure, if the thickness of the test piece is reduced, the test piece of the embodiment and the test piece of the comparative example are confirmed to be degraded in the residual magnetization and the inherent coercive force compared with 0.5 mm. Table 1 shows the ratio of the values of the magnetic properties (residual magnetization) when the thickness of the test piece is 0.2 mm, 0.1 mm, and 0.07 mm to the magnetic properties (residual magnetization) when the thickness of the test piece is 0.5 mm. In addition, Table 2 shows the reduction rate of the residual magnetization.
[0061] According to Table 1, in the test piece of the embodiment, when the thickness of the sample is 0.2 mm, it is 99% when the thickness of the sample is 0.1 mm, and there is almost no degradation. When the thickness of the sample is 0.07 mm, it is 95%, which is slightly degraded. In contrast, it can be seen that the test piece of the comparative example (the test piece made using the sample A and the test piece made using the sample B) is 97% when the thickness of the sample is 0.2 mm, and 83% when the thickness of the sample is 0.07 mm, which is a significant degradation.
[0062] As can be seen, for the test piece of the embodiment, when the thickness of the magnet after processing reaches 0.07mm, the reduction rate of residual magnetization is suppressed to about 5%, and when the thickness of the magnet after processing reaches 0.1mm, the reduction rate of residual magnetization is almost not seen, and it is a high-performance rare earth magnet. Therefore, as described above, the test piece of the embodiment is suitable as a magnet for ultra-small / thin motors, ultra-small / thin magnetic actuators, etc.
[0063] [Table 1]
[0064] Thickness 0.5mm 0.2mm 0.1mm 0.07mm Test pieces of examples 100% 99% 99% 95% Test piece of comparative example (using sample A) 100% 97% 89% 83% Test piece of comparative example (using sample B) 100% 97% 93% 83%
[0065] [Table 2]
[0066] Thickness 0.2mm 0.1mm 0.07mm Test pieces of examples 1% 1% 5% Test piece of comparative example (using sample A) 3% 11% 17% Test piece of comparative example (using sample B) 3% 7% 17%
[0067] Description of Reference Numerals
[0068] 10: crystal grain; 12: crystal grain degraded by grinding; 20: crystal grain; 22: crystal grain degraded by grinding.
Claims
1. A rare earth magnet, obtained by hot plastic working an R-Fe-B alloy containing R, Fe and B, wherein R represents a rare earth element including Nd, The rare earth magnet has R2Fe 14 The structure of the main phase of compound B, The easy magnetization axis is oriented toward the short axis direction of the grains of the main phase. The thickness in the direction of the easy magnetization axis is not less than 0.07 mm and not more than 0.2 mm. The reduction rate of residual magnetization is 5% or less, wherein the reduction rate (%) of residual magnetization is a ratio of the residual magnetization when the thickness of the rare earth magnet is 0.5 mm to 100%.
2. The rare earth magnet according to claim 1, wherein The average crystal grain size of the main phase is 0.02 μm or more and 0.5 μm or less.
3. The rare earth magnet according to claim 1 or 2, wherein: The rare earth magnet has a thickness of 0.1 mm or more and 0.2 mm or less.
4. The rare earth magnet according to claim 1 or 2, wherein: The rare earth magnet is in the shape of a plate.
Citation Information
Patent Citations
Permanent magnet material and its production
JP1987192566A